2020
DOI: 10.1053/j.gastro.2020.06.031
|View full text |Cite|
|
Sign up to set email alerts
|

IRE1A Stimulates Hepatocyte-Derived Extracellular Vesicles That Promote Inflammation in Mice With Steatohepatitis

Abstract: BACKGROUND & AIMS: Endoplasmic reticulum to nucleus signaling 1 (ERN1, also called IRE1A) is a sensor of the unfolded protein response that is activated in the livers of patients with nonalcoholic steatohepatitis (NASH). Hepatocytes release ceramide-enriched inflammatory extracellular vesicles (EVs) after activation of IRE1A. We studied the effects of inhibiting IRE1A on release of inflammatory EVs in mice with diet-induced steatohepatitis. METHODS: C57BL/6J mice and mice with hepatocyte-specific disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 47 publications
5
96
1
Order By: Relevance
“…278 Hepatocytes release ceramide-enriched inflammatory EVs by activating IRE1A, and EVs recruit monocyte-derived macrophages to the liver, resulting in inflammation in mice with steatohepatitis. 279 Thus, lipotoxic injury of hepatocytes boosts the release of EVs and activates macrophages to promote hepatic inflammation, which plays an important role in triggering NAFLD. These findings provide strong support for the development of EVs as biomarkers, and EVs are also potential therapeutic targets and tools.…”
Section: Microbial Dysbiosis and Intestinal Barrier Functionmentioning
confidence: 99%
“…278 Hepatocytes release ceramide-enriched inflammatory EVs by activating IRE1A, and EVs recruit monocyte-derived macrophages to the liver, resulting in inflammation in mice with steatohepatitis. 279 Thus, lipotoxic injury of hepatocytes boosts the release of EVs and activates macrophages to promote hepatic inflammation, which plays an important role in triggering NAFLD. These findings provide strong support for the development of EVs as biomarkers, and EVs are also potential therapeutic targets and tools.…”
Section: Microbial Dysbiosis and Intestinal Barrier Functionmentioning
confidence: 99%
“…On the other hand, tumor cells may hijack the ER-stress pathways to provide survival signals required for uncontrolled growth and eventually avoid apoptosis ( Kim et al, 2015 ). Activation of the UPR has also been shown to affect different fibrotic diseases ( Heindryckx and Li, 2018 ), including non-alcoholic fatty liver disease ( Bandla et al, 2018 ; Kwanten et al, 2016 ; Dasgupta et al, 2020 ), hepatitis-B-induced carcinogenesis ( Li et al, 2017a ), and biliary cirrhosis ( Sasaki et al, 2015 ). We have previously shown that inhibiting the IRE1α-branch of the UPR-pathway using 4μ8C, blocks TGFβ-induced activation of fibroblasts and stellate cells in vitro and reduces liver fibrosis in vivo ( Heindryckx et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the ceramide content in EVs was reported to be higher in patients with steatosis or NASH compared to in obese controls, and ceramide concentrations were nominally higher in NASH patients compared to in patients with only steatosis [ 23 ]. IRE1α activation also increased ceramide synthesis, resulting in augmented EV production and increased hepatic macrophage accumulation in mice with NAFLD [ 25 ]. Moreover, the intravenous injection of these EVs enhanced hepatic macrophage accumulation in otherwise healthy mice [ 25 ].…”
Section: Evs As Mediators Of Nash Progressionmentioning
confidence: 99%
“…IRE1α activation also increased ceramide synthesis, resulting in augmented EV production and increased hepatic macrophage accumulation in mice with NAFLD [ 25 ]. Moreover, the intravenous injection of these EVs enhanced hepatic macrophage accumulation in otherwise healthy mice [ 25 ]. Collectively, this suggests a mechanistic link between EVs released via IRE1α activation and subsequent ceramide synthesis and the hepatic infiltration of macrophages in NAFLD/NASH [ 25 ].…”
Section: Evs As Mediators Of Nash Progressionmentioning
confidence: 99%
See 1 more Smart Citation